Prokineticin 1 is a new biomarker of human oocyte competence: expression and hormonal regulation throughout late folliculogenesis. Issue 4 (5th July 2019) - Alfaidy, Nadia; Baron, Chloé; Antoine, Yannick; Reynaud, Déborah; Traboulsi, Wael; Gueniffey, Aurore; Lamotte, Anna; Melloul, Eve; Dunand, Camille; Villaret, Laure; Bessonnat, Julien; Mauroy, Charlotte; et al.
Abstract: Context: Prokineticin 1 (PROK1) quantification in global follicular fluid (FF) has been recently reported as a predictive biomarker of in vitro fertilization (IVF) outcome. It is now necessary to evaluate its clinical usefulness in individual follicles. Objectives: To evaluate the clinical value of PROK1 secretion in individual FF to predict oocyte competence. To determine the impact of follicular size, oocyte maturity, and gonadotropin treatments on PROK1 secretion. Design and setting: Prospective cohort study from May 2015 to May 2017 at the University Hospital of Grenoble. Patients: A total of 69 infertile couples underwent IVF. Intervention(s): Collection of 298 individual FF from 44 women undergoing IVF; 52 individual cumulus cell (CC) samples and 15 CC primary cultures from 25 women undergoing IVF-intracytoplasmic sperm injection (ICSI). Main Outcome Measure(s): Oocyte competence was defined as the ability to sustain embryo development to the blastocyst stage. Follicular size was measured by 2D-sonography . PROK1 concentration was quantified by ELISA assay. Results: PROK1 concentration was correlated to follicular size (r = 0.85, P = 2.2 × 10 −16 ). Normalized PROK1 concentration in FF was predictive of subsequent oocyte competence (AUROC curve = 0.76 [95% CI, 0.69–0.83]; P = 1.7 × 10 −9 ), irrespectively of day-2 embryo morphokinetic parameters. The expression and secretion of PROK1 were increased in FF and CC of mature oocytes ( P < 0.01). Follicle Stimulating Hormone and hCG up-regulated PROK1 secretion in CC primary cultures ( P < 0.01; P < 0.05), probably through the cAMP pathway ( P < 0.01). Conclusions: PROK1 quantification in individual FF could constitute a new predictive biomarker of oocyte competence in addition with embryo morphokinetic parameters. Trial registration number: none.